OLD AGE, LEGAL CERTAINTY AND CURA DEBILIUM PERSONARUM - PJ Thomas (Obiter, 2022)
Increasing medical costs justify themselves by the success of medical science in assuring greater longevity. We are all aware of the range of socio-economic problems this longer lifespan causes. This paper intends to address a more latent, concomitant strain on the legal system. A few years ago this problem manifested itself in the Supreme Court of Appeal, but passed virtually unnoticed. It is ironic that this instance, that is, the Saayman case (Eerste Nasionale Bank van Suidelike Afrika Bpk v Saayman NO 1997 4 SA 302 (HHA)) will be long remembered on account of the minority judgment by Olivier JA. The enlightened approach by the late judge was rejected by the majority of the court in its endeavour to safeguard legal certainty. While legal certainty is indeed one of the important foundations of a legal system as it embodies the fundamental principle of equality before the law and provides predictability, which is an essential characteristic of science and facilitates planning, it should not be the ultimate objective at the expense of justice. Moreover, by virtue of the law of unintended consequences, the Supreme Court of Appeal dealt a vicious blow to legal certainty as well as to the legal capacity of senior citizens in this decision, which clearly set out the law applicable to this increasing segment of the population.It is with gratitude to the editors of Obiter that I dedicate this essay to the memory of Lappies aka Professor JMT Labuschagne, who was for over 30 years my colleague at the University of Pretoria. The wide range of his intellect-tual curiosity and his deep humanity not only made him a prolific author, but a friend whose comments were always characterised by wisdom and kindness.